The impact of taxes and regulations on firm births and deaths in state border counties. Issue 1 (11th April 2016) - Crum, Michael; Gohmann, Stephan F
Abstract : Purpose: – The purpose of this paper is to examine the influence of the institutional environment on firm birth and death rates. It is hypothesized that high taxation levels, large government size, high levels of unionization and high minimum wages will be associated with relatively low firm birth and death rates. Design/methodology/approach: – This study makes use of a set of custom tabulations from the US Census Bureau that contain data on county-level firm births and deaths. To account for differences in state policies, matched contiguous counties located on state borders are used to calculate matched birth and death ratios. Findings: – In the sample of eastern US state border counties, state taxation levels and minimum wages had no significant relationship with firm birth rates, but there was a negative relationship between state union densities and firm birth rates. Both state education and public welfare expenditures were marginally negatively related to firm birth rates. State public welfare expenditures were negatively related to firm death rates, while a marginally significant negative relationship between hospital/health expenditures and firm death rates was observed. Research limitations/implications: – These results indicate that state government expenditures may have varying influences on firm birth and death rates, and that high union densities may deter new firm entry. Originality/value: – This paper makes use of a county matching technique to help control for confounding variables, allowing for differences in state policies to be better accounted for.